Fingerprinting FTIR-ATR Fraksi Kopi Robusta dan Arabika serta Korelasinya terhadap Aktivitas Antioksidan - Masjuwina Simatupang; Dian Herawati; Nancy Dewi Yuliana (Jurnal Teknologi dan Industri Pangan, 2023)
Coffee has a positive effect on health due to its high content of antioxidant compounds. The potential antioxidant activity of coffee is strongly influenced by its chemical compound profile. This study aimed to analyze the effect of different solvents on the chemical metabolites profile, antioxidant activity, and to determine the relevant chemical functional groups which positively contribute to the coffee’s antioxidant activity. In this study, methanolic extract of coffee samples from robusta and arabica varieties were fractionated by liquid-liquid fractionation method using four solvents with different polarities. ABTS (2,2'-azinobis (3-ethylbenzothiazoline-6-sulphonic acid) and cupric reducing antioxidant capacity (CUPRAC) assays were applied to measure the antioxidant activity of the coffee fractions. Fourier Transform Infrared- Attenuated Total Reflectance (FTIR-ATR) based chemometric approach was used to identify the compound functional groups as the fingerprinting profile of the coffee fractions. Correlation between the FTIR-ATR fingerprinting with the antioxidant activity of the coffee fractions was studied using multivariate data analysis, i.e. Principal Component Analysis (PCA) and Orthogonal Partial Least Squares (OPLS). From this study, a reliable PCA model to evaluate the effect of different solvents to FTIR-ATR fingerprinting profile was produced. The correlation between FTIR-ATR fingerprinting profile with the antioxidant activity and the characterization of the chemical functional groups relevant to its antioxidant activity can be analyzed by a reliable OPLS model obtained. This study suggests that the highest antioxidant potential in coffee is found in ethyl acetate fraction both in robusta and arabica coffee samples, while the relevant chemical functional groups having positive correlation to antioxidant activity of coffee were phenol, carbonyl, cyclohexane, aromatic, amide, phenyl, amino, and alkene groups.